2015
DOI: 10.5897/ijps2015.4384
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational effect on surface waves in a homogeneous fibre-reinforced anisotropic general viscoelastic media of higher and fractional order with voids

Abstract: In this paper, gravitational effects on propagation of surface waves in a homogeneous fibrereinforced anisotropic general viscoelastic media of higher order with voids is investigated. The general surface wave speed is derived to study the effects of gravity on surface waves. Particular cases for Stoneley and Rayleigh waves are discussed. The results obtained in this investigation are more general in the sense that some earlier published results are obtained from our result as special cases. In the absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Singh [6] studied the reflection and transmission of couple longitudinal waves at a plane interface between two dissimilar half-spaces of thermo-elastic materials with voids. Khan et al [7] observed the gravitational effect on surface waves in homogeneous fibrereinforced anisotropic general viscoelastic media of higher and fractional order with voids. Rani et al [8] studied the torsional vibrations of initially stressed composite poroelastic cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…Singh [6] studied the reflection and transmission of couple longitudinal waves at a plane interface between two dissimilar half-spaces of thermo-elastic materials with voids. Khan et al [7] observed the gravitational effect on surface waves in homogeneous fibrereinforced anisotropic general viscoelastic media of higher and fractional order with voids. Rani et al [8] studied the torsional vibrations of initially stressed composite poroelastic cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…These elements are so tightly connected to one another that there is no mutual mobility across them. Some commendable models signifying the properties of fiber composites and their impact are included in other studies [21][22][23]. Viscoelasticity is a ubiquitous feature of diverse crustal rocks that makes it a significant contribution to seismic wave attenuation.…”
mentioning
confidence: 99%